PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PADA 212 MART BANJARMASIN - Rahmat Hilmi (Kresna Bina Insan Prima, 2020)
The purpose of this study was to determine the effect of independent variables consisting of Product, Price, Place and Promotion both simultaneously and partially on the dependent variable of purchasing decisions at 212 Mart Banjarmasin. As well as wanting to find out the dominant variables affecting purchasing decisions at 212 Mart Banjarmasin. The data used is the result of distributing questionnaires to respondents who shop at 212 Mart Banjarmasin. The sample selection technique is Accindental Sampling with a total of 70 consumers. Data processing techniques using SPSS (Statistical Package for the Social Sciences). The results showed that simultaneously the Product, Price, Place and Promotion variables significantly influenced the purchase decision variable at 212 Mart Banjarmasin at 14,671. Partially only the place variable influences the purchase decision at 212 Mart Banjarmasin, which is 3.255 with a significance value of 0.002. While the Product variable (0.856), Price (1,627) and Promotion (1,624) have no significant effect on purchasing decisions at 212 Mart Banjarmasin. The dominant influential variable is the Place with Beta Value on Standardized Coefficients (0.382), meaning that according to consumers' perception the place factor becomes something that is considered important in an effort to create a purchasing decision at 212 Mart. Referring to the termination coefficient (R Square) of 0.456, the purchase decision at 212 Mart 45.6% is influenced by product variables, price, place and promotion. While the remaining 45.4% of consumer purchasing decisions are influenced by other variables not included in this study.